Mycobacterium tuberculosis pellicles express unique proteins recognized by the host humoral response. Issue 3 (26th February 2014) - Kerns, Patrick W.; Ackhart, David F.; Basaraba, Randall J.; Leid, Jeff G.; Shirtliff, Mark E.
Abstract Mycobacterium tuberculosis (MTB) causes both acute and chronic infections in humans characterized by tolerance to antibiotics and reactivation to cause secondary tuberculosis. These characteristics have led to renewed interest in the in vitro pellicle, or biofilm mode of growth, where bacteria grow to produce a thick aggregate at the air–liquid interface and exhibit increased phenotypic resistance to antibiotics. We infected guinea pigs with the virulent H37Rv strain of MTB for 60 days at which point we collected blood. To identify antigenic proteins, membrane protein extracts of MTB H37Ra pellicles and shaken cultures grown for 3, 5, or 7 weeks were probed with the infected animals' sera after the proteins were separated by two‐dimensional gel electrophoresis (2DGE). Antigenic proteins were then identified using MALDI‐TOF/TOF mass spectrometry peptide mass fingerprinting. Antigenic pellicle proteins were compared across the three timepoints to identify those that were produced consistently during pellicle growth. They were also compared to those membrane proteins identified from harvested shaken cultures to determine pellicle‐specific vs. universally expressed proteins. Using this technique, we identified 44 distinct antigenic proteins, nine of which were pellicle‐specific. The sequence of antigenic pellicle‐specific proteins was checked for sequence conservation across 15 sequenced MTB clinical isolates, three other members of the MTB complex, as well as M. avium and M. smegmatis. The antigenic pellicle‐specific protein Rv0097 was found to have very high sequence conservation within the MTB complex but not with related mycobacteria, while FabG4 was highly conserved in all mycobacteria analyzed. These conserved pellicle‐specific proteins represent targets for the development of future diagnostic tests and vaccines.